Effects of Plant and Soil Characteristics on Phyllosphere and Rhizosphere Fungal Communities During Plant Development in a Copper Tailings Dam - Jia, Tong; Yao, Yushan; Guo, Tingyan; Wang, Ruihong; Chai, Baofeng (Frontiers in Microbiology, 2020)
Interactions between plants and microbes can affect ecosystem functions, and many studies have demonstrated that plant properties influence mutualistic microorganisms. Here, high-throughput sequencing was used to investigate rhizosphere and phyllosphere fungal communities during different plant development stages. Results demonstrated that phyllosphere and rhizosphere fungal community structures were distinct during all developmental stages while they were mediated separately by plant carbon and soil sulfur. Comparatively, the effect of root properties on phyllosphere fungal diversity was greater than soil properties. Moreover, rhizosphere fungal networks of Bothriochloa ischaemum were more complex than phyllosphere fungal networks. This study demonstrated that the effect of plant and soil traits on phyllosphere and rhizosphere fungal communities could potentially be significant, depending on the applicable environmental condition and plant development stage. Although links between phyllosphere and rhizosphere communities have been established, further studies on functional fungal groups during phytoremediation processes are necessary. This study comprehensively analyzed dynamic relationships between phyllosphere and rhizosphere fungal communities during different plant development stages in a polluted environment. These fungal communities were determined to be expedient to the development and utilization of beneficial microbial communities during different development stages, which could more effectively help to stabilize and reclaim contaminated copper tailings soil.